2021
DOI: 10.1186/s12906-021-03268-4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and complementary medicine use among chronic haemodialysis patients: a nationwide cross-sectional study

Abstract: Background In the era of digital and improved conventional medicine, many continue to use traditional and complementary medicine (TCM). The prevalence of its usage is not well reported, especially in patients with end-stage kidney disease (ESKD) receiving haemodialysis, thus its benefits and adverse effects are not widely known. This study determines the prevalence, types, perceptions and factors associated with TCM use by chronic haemodialysis patients in Malaysia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 26 publications
5
12
1
Order By: Relevance
“…We observed that most of the CAM use was undisclosed to the treating physician, as has been reported previously [ 19 , 20 , 23 ]. The reasons for this attitude include the assumption that their physician would disapprove of it (38.2%) or that the physician did not believe in it (33.3%).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We observed that most of the CAM use was undisclosed to the treating physician, as has been reported previously [ 19 , 20 , 23 ]. The reasons for this attitude include the assumption that their physician would disapprove of it (38.2%) or that the physician did not believe in it (33.3%).…”
Section: Discussionsupporting
confidence: 83%
“…This high prevalence of CAM use in our setting probably reflects the high prevalence of CAM use in the general population. Indeed, the prevalence of CAM use varies according to the cultural beliefs and practices of different populations [ 19 ]. Among the general population in Cameroon, the prevalence of CAM use was reported to be 80%, similar to our results [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations